Isolasi dan Skrining Bakteri Indigenous dari Air Rendaman Pelepah Tanaman Salak (Zalacca edulis, Reinw.) yang berpotensi sebagai Bakteri Selulolitik - Anggraeni, Imelda Lusi, Triastuti Rahayu, S.Si., M.Si (2015)
Cellulolytic bacteria are bacteria which produce cellulase enzyme which functioned to degrade cellulose. Cellulolytic bacteria can be found in the decomposing plant tissue. This study aims to determine the potential of the cellulolytic and the characteristics of the bacteria from the result of the isolation and screening of indigenous bacteria from the immersion water of Zalacca (Zalacca edulis, Reinw.) plant stem. The parameters that are used in this study are the isolates of indigenous bacteria that have potential as cellulolytic bacteria and cellulolytic bacterial characteristics. This study is an exploratory study, the obtained data is systematically collected and presented informatively. The study is done by isolating the bacteria by using Gelatine Nutrient media to get the bacteria with different characteristics and then the screening by using 1% of Gelatine Carboxy Methyl Cellulose (Gelatine CMC) selective media with 0.1% of Congo red indicator, incubated on 280C for five days (Cellulolytic bacteria were marked by the emergence of a clear zone around the colony). The results of the isolation and screening of the bacteria are the seven isolates which have different characteristics, and all of the isolates are able to degrade cellulose. The largest cellulolytic activity index on the cellulolytic bacteria coded S3 is 1.27 mm. The shapes of the seven isolates of cellulolytic bacteria are all in coccus shapes with three types of gram-negative and four types of gram-positive.